A coating liquid and a preparation method thereof and application thereof in preparing a corrosion-resistant coating on the surface of a quartz part
Through the coating solution composed of nano-grade silicon carbide and α-Al2O3 solution on the surface of the quartz parts, and it is carried out by fire, forming corrosion-resistant coating, solving the surface corrosion layer of the quartz tube in solar cell chips caused The problem has significantly improved the high temperature performance and service life of quartz parts.
Patent Information
- Application Number
- CN202410995926.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-24
AI Technical Summary
The corrosion layer generated on the surface of the quartz tube in the high temperature process of solar cell cells causes the pipe to rupture. The existing technology is difficult to effectively solve this problem, which seriously affects the service life of the quartz tube.
Provides a coating solution, including nano-level silicon carbide, α-Al2O3 solitude, pure water and surface active agents. It forms corrosion-resistant coating on the surface of quartz parts by spraying and fire polishing to improve its high temperature and corrosion resistance.
By forming a dense corrosion -resistant coating on the surface of the quartz parts, the corrosion resistance performance and service life of quartz parts in high -temperature processes are significantly improved, and the deformation and rupture of the pipe are avoided.
Smart Images

Figure CN118772671B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of quartz parts processing, and in particular to a coating liquid and a preparation method thereof and application thereof in preparing a corrosion-resistant coating on the surface of a quartz part. Background Art
[0002] Solar cells use large-sized quartz tubes as carriers in high-temperature processes such as sintering, coating and oxidation. In the above-mentioned high-temperature processes, the operating temperature range of the quartz tube is around 1000°C. As the number of uses increases, the quartz tube will deform. At the same time, during use, corrosive gases such as silane, phosphine, and ammonia will be introduced into the quartz tube. After long-term high-temperature use, these corrosive gases will corrode the surface of the tube, causing a thick corrosion layer to appear on the surface of the tube. The formation of the corrosion layer will weaken the structural strength of the quartz tube, making the quartz tube more prone to rupture when subjected to internal pressure or external impact. In addition, the corrosion layer may change the geometry of the quartz tube, leading to stress concentration, further increasing the risk of rupture, and thus seriously affecting the service life of the quartz tube.
[0003] The existing technical solutions are mainly used to solve the problem of quartz tube deformation under long-term high-temperature use. However, the problem of tube rupture caused by the corrosion layer on the surface of the quartz tube during the high-temperature process of solar cells has not been effectively solved, which seriously affects the service life of the tube.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgement or any form of suggestion that the information constitutes the prior art already known to ordinary technicians in this field. Summary of the invention
[0005] Purpose of the invention: The technical problem to be solved by the present invention is to address the deficiencies in the prior art and to provide a coating liquid and a preparation method thereof and their application in preparing a corrosion-resistant coating on the surface of quartz parts, so as to solve the problem of the corrosion layer generated on the surface of the quartz tube in the high-temperature process of solar cells causing the tube to rupture.
[0006] In order to solve the above technical problems, the first aspect of the present invention discloses a coating liquid, which includes nano-scale silicon carbide, pure water, a surfactant and α-Al2O3 sol.
[0007] Specifically, the coating liquid includes the following components in weight percentage:
[0008] Nano-scale silicon carbide 10%-15wt%;
[0009] Pure water 70wt%-77wt%;
[0010] Surfactant 3wt%-5wt%;
[0011] α-Al2O3 sol 10wt%-15wt%.
[0012] Specifically, the nano-scale silicon carbide is selected from any one of black silicon carbide and green silicon carbide or a combination of both; the nano-scale is 50nm-100nm.
[0013] Specifically, the surfactant is any one or a combination of triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, polyacrylamide, polyvinyl alcohol and polyethylene glycol.
[0014] Specifically, the solid content of the α-Al2O3 sol is in the range of 15wt% to 25wt%, preferably, the solid content is 20wt%.
[0015] The second aspect of the present invention also provides a method for preparing the coating liquid provided in the first aspect, wherein the raw materials according to the formula amount are stirred and mixed.
[0016] Specifically, the stirring speed is 500 rpm to 600 rpm, and the stirring time is 1 to 2 hours.
[0017] The third aspect of the present invention also provides the use of the coating liquid provided in the second aspect to prepare a corrosion-resistant coating on the surface of a quartz part.
[0018] Specifically, it includes the following steps:
[0019] Pretreatment step: performing sandblasting pretreatment on the area to be coated on the surface of the quartz part;
[0020] Spraying step: spraying the coating liquid on the area to be coated on the surface of the quartz part to form a first material layer;
[0021] Melting and solidifying step: performing fire polishing on the first material layer, so that the first material layer is melted and solidified in the area to be coated on the surface of the quartz part to form a corrosion-resistant coating, thereby obtaining a corrosion-resistant quartz part.
[0022] Specifically, the sandblasting abrasive for the sandblasting pretreatment is silicon carbide.
[0023] Specifically, the particle size of the silicon carbide is 20nm-50nm.
[0024] Furthermore, after the melting and solidification step, the method further includes performing an acid wash treatment on the corrosion-resistant quartz part to wash away surface impurities of the corrosion-resistant quartz part.
[0025] Specifically, the quartz part is a high-purity quartz part, in which the content of silicon dioxide is more than 99.99wt%, and the total content of metal impurities is ≤20ppm.
[0026] Specifically, the fire polishing temperature of the fire polishing treatment is controlled at 1000° C. to 1500° C., and the fire polishing treatment time is controlled at 2-4 hours.
[0027] Specifically, the quartz part is a quartz tube.
[0028] Beneficial effects:
[0029] 1) The present invention forms a first material layer by spraying a coating liquid prepared with nano-scale silicon carbide, α-Al2O3 sol and an additive on the area to be coated on the surface of a quartz part; the first material layer is subjected to fire polishing treatment, so that the first material layer is melted and solidified in the area to be coated on the surface of the quartz part to form a dense corrosion-resistant coating, thereby obtaining a corrosion-resistant quartz part. The present invention adds α-Al2O3 to the coating liquid, so that the corrosion-resistant coating includes cristobalite generated by α-Al2O3 and quartz glass at high temperature, and cristobalite helps to improve high temperature resistance. At the same time, during the fire polishing treatment, α-Al2O promotes α-SiC to transform into β-SiC under high temperature. Compared with α-SiC, the structure of β-SiC is more stable and its corrosion resistance is more excellent. In addition, in the corrosion-resistant coating, cristobalite and β-SiC are closely combined, making the corrosion-resistant coating dense. Therefore, compared with high-purity quartz tubes, the corrosion-resistant coating makes the produced corrosion-resistant quartz parts such as tubes suitable for high-temperature processes of solar cells, while improving their high-temperature performance and significantly improving their corrosion resistance in high-temperature processes of solar cells.
[0030] 2) In the present invention, the area to be coated on the surface of the quartz part is pre-treated by sandblasting with silicon carbide, so that the area to be coated can achieve a uniform and dense structure and improve the adhesion of the silicon carbide coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0032] Figure 1 This is a scanning electron microscope image of the corrosion-resistant coating in Example 1 of the present invention.
[0033] Figure 2 for Figure 1 X-ray diffraction pattern of the corrosion resistant coating shown.
[0034] Figure 3 This is the X-ray diffraction pattern of the silicon carbide coating in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0035] As analyzed in the background technology of this application, the existing technology methods are difficult to solve the problem of the corrosion layer on the surface of the quartz tube in the high-temperature process of the solar cell causing the tube to rupture. In order to solve this problem, this application provides a coating liquid and a preparation method thereof and its application in preparing a corrosion-resistant coating on the surface of a quartz part.
[0036] Example 1
[0037] This embodiment provides a coating liquid, which includes nano-scale black silicon carbide, α-Al2O3 sol, pure water and triethylhexyl phosphoric acid.
[0038] In this embodiment, the coating liquid includes the following components in weight percentage: 10% nano-scale black silicon carbide; 77wt% pure water; 3wt% triethylhexyl phosphoric acid; 10wt% α-Al2O3 sol. In this embodiment, the solid content of α-Al2O3 sol is 20%. The above components are stirred at a mechanical stirring speed of 500rpm for 2h to prepare the coating liquid of this embodiment.
[0039] This embodiment also provides an application of the coating liquid to prepare a corrosion-resistant coating on the surface of a quartz part. In this embodiment, the quartz part is a high-purity quartz tube, in which the content of silicon dioxide is more than 99.99wt%, and the total content of metal impurities is ≤20ppm.
[0040] The method of the application comprises the following steps:
[0041] Pretreatment step: performing sandblasting pretreatment on the area to be coated on the surface of the quartz part;
[0042] Spraying step: spraying the coating liquid prepared in this embodiment on the area to be coated on the surface of the quartz part to form a first material layer;
[0043] Melting and solidifying step: performing fire polishing on the first material layer, so that the first material layer is melted and solidified in the area to be coated on the surface of the quartz part to form a corrosion-resistant coating, thereby obtaining a corrosion-resistant quartz part.
[0044] Specifically, the sandblasting abrasive used in the sandblasting pretreatment is 50 nm silicon carbide.
[0045] Specifically, in the spraying step, the coating liquid prepared in this embodiment is loaded into the spray pot of the spray gun, and the spray gun is installed on the synchronous belt. The synchronous belt drives the spray gun to move forward at a uniform speed along the axial direction of the quartz tube. At the same time, the graphite wheel will rotate at a certain speed along with the tube, and the coating liquid prepared in this embodiment is evenly sprayed onto the surface of the quartz tube, forming a silicon carbide material layer with uniform thickness on the surface of the quartz tube.
[0046] Specifically, in the melting and solidification step, the first material layer is subjected to fire polishing treatment using a quartz burner, the fire polishing temperature of the fire polishing treatment is controlled at 1500° C., and the fire polishing treatment time is controlled at 3 hours.
[0047] Specifically, the area to be coated on the surface of the quartz part is the outer surface of the high-purity quartz tube. The diameter of the high-purity quartz tube is 440 mm. Figure 1 As shown, the thickness of the corrosion-resistant coating formed on the area to be coated on the surface of the quartz part is 22 μm. The use conditions of the corrosion-resistant quartz parts obtained in this embodiment are as follows: the corrosion-resistant quartz tube is fixed in a tubular furnace, the flanges at both ends are sealed, and a mixed gas containing monosilane, diborane and phosphine is introduced. The total flow rate of the mixed gas is 100 ml / min, and the temperature is raised to 1000°C. Under the above-mentioned use conditions, the corrosion-resistant quartz tube prepared in this embodiment was used continuously for 120 days, and the tube did not experience deformation, fracture or other problems. The X-ray diffraction pattern of the corrosion-resistant coating obtained in this embodiment is shown in the figure. Figure 2 As shown by Figure 2 It can be found that the first strong peak is 35.64°, the second strong peak is 60°, and the third strong peak is 71.78°. Their corresponding intensities are 6810CPS, 2476CPS, and 1688CPS, respectively, which are consistent with the angles and intensities of the corresponding peaks of β-silicon carbide. Therefore, it can be judged that the silicon carbide crystal form in the corrosion-resistant coating is β-SiC.
[0048] In this embodiment, α-Al2O3 is added to the coating liquid, so that the corrosion-resistant coating includes cristobalite generated by α-Al2O3 and quartz glass at high temperature, and cristobalite helps to improve the high temperature resistance. At the same time, during the fire polishing process, α-Al2O promotes α-SiC to transform into β-SiC under high temperature. Compared with α-SiC, the structure of β-SiC is more stable and its corrosion resistance is better. In addition, in the corrosion-resistant coating, cristobalite and β-SiC are closely combined, making the corrosion-resistant coating dense. Therefore, compared with the high-purity quartz tube body, the corrosion-resistant coating makes the obtained corrosion-resistant quartz parts such as pipe fittings suitable for the high-temperature process of solar cells, while improving its high-temperature performance, it significantly improves its corrosion resistance in the high-temperature process of solar cells.
[0049] Furthermore, after the melting and solidification step, the corrosion-resistant quartz part is pickled to remove surface impurities of the corrosion-resistant quartz part to avoid contamination to subsequent processes.
[0050] Example 2
[0051] Different from Example 1, the coating liquid of this example includes the following components in weight percentage: 11% of nano-scale green silicon carbide; 75wt% of pure water; 4wt% of triethylhexyl phosphoric acid; 10wt% of α-Al2O3 sol. In this example, the solid content of α-Al2O3 sol is 20%. The above components are stirred at a mechanical stirring speed of 500rpm for 2h to prepare the coating liquid of this example.
[0052] This embodiment also provides an application of the coating liquid to prepare a corrosion-resistant coating on the surface of a quartz part. In this embodiment, the quartz part is a high-purity quartz tube, in which the silicon dioxide content is more than 99.99wt%, and the total content of metal impurities is ≤20ppm. Repeat the application method in Example 1 to prepare a corrosion-resistant coating on the surface of a high-purity quartz tube using the coating liquid provided in this embodiment, to obtain the corrosion-resistant quartz tube of this embodiment. The quartz tube body size of the corrosion-resistant quartz tube is the same as the quartz tube body size in Example 1, and the thickness of its corrosion-resistant coating is the same as the thickness of the corrosion-resistant coating in Example 1. The corrosion-resistant quartz tube of this embodiment was used continuously for 120 days under the same use conditions as Example 1, and the tube did not deform or break.
[0053] Example 3
[0054] Different from Example 2, the coating liquid of this example includes the following components in weight percentage: 12% of nano-scale green silicon carbide; 70wt% of pure water; 5wt% of triethylhexyl phosphoric acid; 13wt% of α-Al2O3 sol. In this example, the solid content of α-Al2O3 sol is 20%. The above components are stirred at a mechanical stirring speed of 500rpm for 2h to prepare the coating liquid of this example.
[0055] This embodiment also provides an application of the coating liquid to prepare a corrosion-resistant coating on the surface of a quartz part. In this embodiment, the quartz part is a high-purity quartz tube, in which the content of silicon dioxide is more than 99.99wt%, and the total content of metal impurities is ≤20ppm. Repeat the application method in Example 1 to prepare a corrosion-resistant coating on the surface of a high-purity quartz tube using the coating liquid provided in this embodiment, to obtain the corrosion-resistant quartz tube of this embodiment. The quartz tube body size of the corrosion-resistant quartz tube is the same as the quartz tube body size of Example 1, and the thickness of the corrosion-resistant coating is the same as the thickness of the corrosion-resistant coating of Example 1. The corrosion-resistant quartz tube of this embodiment was used continuously for 120 days under the same use conditions as Example 1, and the tube did not deform or break.
[0056] Example 4
[0057] Different from Example 1, the coating liquid of this example includes the following components in weight percentage: 10% nano-scale green silicon carbide; 70wt% pure water; 3wt% polyvinyl alcohol; 10wt% α-Al2O3 sol. In this example, the solid content of the α-Al2O3 sol is 20%. The above components are stirred at a mechanical stirring speed of 500rpm for 2h to prepare the coating liquid of this example.
[0058] This embodiment also provides an application of the coating liquid to prepare a corrosion-resistant coating on the surface of a quartz part. In this embodiment, the quartz part is a high-purity quartz tube, in which the content of silicon dioxide is more than 99.99wt%, and the total content of metal impurities is ≤20ppm. Repeat the application method in Example 1 to prepare a corrosion-resistant coating on the surface of a high-purity quartz tube using the coating liquid provided in this embodiment to obtain the corrosion-resistant quartz tube of this embodiment. The quartz tube body of the corrosion-resistant quartz tube is the same size as the quartz tube body of Example 1, and the thickness of its corrosion-resistant coating is the same as the thickness of the corrosion-resistant coating of Example 1. The corrosion-resistant quartz tube of this embodiment was used continuously for 120 days under the same use conditions as Example 1, and the tube did not deform or break.
[0059] Example 5
[0060] Different from Example 1, the coating liquid of this example includes the following components in weight percentage: 10% nano-scale green silicon carbide; 70wt% pure water; 3wt% polyethylene glycol; 10wt% α-Al2O3 sol. In this example, the solid content of the α-Al2O3 sol is 20%. The above components are stirred at a mechanical stirring speed of 500rpm for 2h to prepare the coating liquid of this example.
[0061] This embodiment also provides an application of the coating liquid to prepare a corrosion-resistant coating on the surface of a quartz part. In this embodiment, the quartz part is a high-purity quartz tube, wherein the silicon dioxide content is more than 99.99wt%, and the total content of metal impurities is ≤20ppm. Repeat the application method in Example 1 to prepare a corrosion-resistant coating on the surface of a high-purity quartz tube using the coating liquid provided in this embodiment to obtain the corrosion-resistant quartz tube of this embodiment. The quartz tube body of the corrosion-resistant quartz tube is the same size as the quartz tube body of Example 1, and the thickness of its corrosion-resistant coating is the same as the thickness of the corrosion-resistant coating of Example 1. The corrosion-resistant quartz tube of this embodiment was used continuously for 120 days under the same use conditions as Example 1, and the tube did not deform or break.
[0062] Example 6
[0063] In this embodiment, the coating liquid includes the following components in weight percentage: 10% nano-scale green silicon carbide; 70wt% pure water; 3wt% triethylhexyl phosphoric acid; 10wt% α-Al2O3 sol. Different from the solid content of the α-Al2O3 sol in Example 1, in this embodiment, the solid content of the α-Al2O3 sol is 25%. The above components are stirred at a mechanical stirring speed of 500rpm for 2h to prepare the coating liquid of this embodiment.
[0064] This embodiment also provides an application of the coating liquid to prepare a corrosion-resistant coating on the surface of a quartz part. In this embodiment, the quartz part is a high-purity quartz tube, in which the content of silicon dioxide is more than 99.99wt%, and the total content of metal impurities is ≤20ppm. Repeat the application method in Example 1 to prepare a corrosion-resistant coating on the surface of a high-purity quartz tube using the coating liquid provided in this embodiment to obtain the corrosion-resistant quartz tube of this embodiment. The quartz tube body size of the corrosion-resistant quartz tube is the same as the quartz tube body size in Example 1, and the thickness of its corrosion-resistant coating is the same as the thickness of the corrosion-resistant coating in Example 1. The corrosion-resistant quartz tube of this embodiment was used continuously for 120 days under the same test conditions as Example 1, and the tube did not deform or break.
[0065] Comparative Example 1
[0066] The uncoated high-purity quartz tube of the same size and batch number provided in Example 1 was used continuously for 60 days under the same conditions as in Example 1, and the tube was deformed and broken.
[0067] Comparative Example 2
[0068] In this comparative example, the coating liquid includes the following components in weight percentage: 20% α-Al2O3 sol; 75% pure water; 5% triethylhexyl phosphate. The above components are stirred at a stirring speed of 500 rpm for 2 hours to obtain the α-Al2O3 coating liquid of this comparative example.
[0069] The α-Al2O3 coating liquid is used to prepare a coating on the surface of a high-purity quartz tube, comprising the following steps:
[0070] The α-Al2O3 coating liquid is loaded into the spray pot of the spray gun, and the spray gun is installed on the synchronous belt. The synchronous belt drives the spray gun to move forward at a uniform speed along the axial direction of the quartz tube. At the same time, the graphite wheel will rotate at a certain speed along with the tube, and the coating liquid is evenly sprayed onto the surface of the quartz tube, forming an α-Al2O3 material layer with uniform thickness on the surface of the quartz tube;
[0071] The coated tube is fire-polished by using a quartz blowtorch, and the fire-polishing temperature is controlled at 1500°C, so that the α-Al2O3 material layer is melted and solidified on the surface of the quartz tube to form a high-temperature resistant coating, thereby obtaining an α-Al2O3 coated quartz tube. The quartz tube body size of the α-Al2O3 coated quartz tube is the same as that of the quartz tube body of this embodiment 1, and the thickness of its high-temperature resistant coating is the same as that of the corrosion-resistant coating of embodiment 1.
[0072] The α-Al2O3 coated quartz tube thus obtained was used continuously for 60 days under the same conditions as in Example 1, and the tube broke but did not deform.
[0073] Compared with Example 1, the quartz coated tube prepared in this comparative example has only one layer of high temperature resistant coating on its surface. Therefore, under the same use conditions, the tube was only used for 60 days, and corrosion and fracture occurred in the tube, but no deformation occurred.
[0074] Comparative Example 3
[0075] In this comparative example, the coating liquid includes the following components in weight percentage: 20% nano-scale green silicon carbide; 5% triethylhexyl phosphoric acid; 75% pure water. The above components are stirred at a stirring speed of 500 rpm for 2 hours to obtain the silicon carbide coating liquid of this comparative example.
[0076] The coating liquid prepared in this comparative example is used to prepare a coating on the surface of a high-purity quartz tube, comprising the following steps:
[0077] The high purity quartz tube provided was sandblasted using 2000 mesh silicon carbide;
[0078] The coating liquid prepared in this comparative example is loaded into the spray pot of the spray gun, and the spray gun is installed on the synchronous belt. The synchronous belt drives the spray gun to move forward at a uniform speed along the axial direction of the quartz tube. At the same time, the graphite wheel rotates at a certain speed along with the tube, and the coating liquid prepared in this example is evenly sprayed onto the surface of the quartz tube, forming a silicon carbide material layer with uniform thickness on the surface of the quartz tube;
[0079] The coated tube is fire-polished by using a quartz blowtorch, and the fire-polishing temperature is controlled at 1500° C., and a silicon carbide coating is formed on the surface of the quartz tube to obtain a silicon carbide coated quartz tube. The quartz tube body size of the silicon carbide coated quartz tube is the same as that of the quartz tube body of this embodiment 1, and the thickness of the silicon carbide coating is the same as that of the corrosion-resistant coating of embodiment 1.
[0080] The silicon carbide coated quartz tube thus obtained was used continuously at a high temperature of 1000°C for 90 days, and the tube deformed and broke.
[0081] Compared with Example 1, the silicon carbide coated quartz tube prepared in this comparative example has only one layer of α-SiC coating. The X-ray diffraction pattern of the silicon carbide layer in the silicon carbide coated quartz tube obtained in this example is as follows: Figure 3 As shown by Figure 3 It can be found that the first strong peak is 35.60°, the second strong peak is 59.96°, and the third strong peak is 34.08°, and their corresponding intensities are 5772CPS, 1946CPS and 1772CPS, respectively, which are consistent with the strong peak angles and intensities corresponding to the α-type silicon carbide crystal form. It can be judged that the crystal form of the silicon carbide coating prepared in this comparative example belongs to α-SiC.
[0082] After the silicon carbide coated quartz tube prepared in this comparative example was used continuously for 90 days under the same conditions as in Example 1, the silicon carbide coated quartz tube was corroded and fractured, and deformation occurred at the same time. Therefore, it can be seen that the service life of the silicon carbide coated quartz tube prepared in this comparative example is 90 days, which is shorter than 120 days in Example 1.
[0083] In this embodiment, because the corrosion resistance and high temperature resistance of the α-SiC coating are much lower than the corrosion-resistant coating in the corrosion-resistant quartz tube prepared in Example 1, under the same production process conditions, the service life of the silicon carbide coated quartz tube is much lower than that of the corrosion-resistant quartz tube prepared in Example 1.
[0084] The present invention provides a coating liquid and a preparation method thereof, and a method and idea for using the same to prepare a corrosion-resistant coating on the surface of a quartz part. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be considered as the scope of protection of the present invention. All components not specified in this embodiment can be implemented using existing technologies.
Claims
1. Application of a coating liquid in preparing a corrosion-resistant coating on the surface of a quartz part, characterized in that: The steps include: Pretreatment step: sandblasting pretreatment of the surface of the quartz part in the area to be coated; Spraying step: spraying the coating liquid on the area to be coated on the surface of the quartz part to form a first material layer; the coating liquid includes the following components in weight percentage: Nano-scale silicon carbide 10%-15wt%; Pure water 70wt%-77wt%; Surfactant 3wt%-5wt%; α-Al2O3 sol 10wt%-15wt%; Melting and solidifying step: performing fire polishing treatment on the first material layer, so that the first material layer is melted and solidified in the area to be coated on the surface of the quartz part to form a corrosion-resistant coating, thereby obtaining a corrosion-resistant quartz part; the fire polishing temperature of the fire polishing treatment is controlled at 1000°C~1500°C, and the fire polishing treatment time is controlled at 2-4h.
2. The use according to claim 1, characterized in that: The quartz part is a quartz tube body.
3. The use according to claim 1, characterized in that: The nano-scale silicon carbide is selected from any one of black silicon carbide and green silicon carbide or a combination of the two; the nano-scale is 50nm-100nm.
4. The use according to claim 3, characterized in that: The surfactant is any one or a combination of triethylhexyl phosphate, sodium lauryl sulfate, methyl amyl alcohol, polyacrylamide, polyvinyl alcohol and polyethylene glycol.
5. The use according to claim 1, characterized in that: The solid content of the α-Al2O3 sol is in the range of 15wt% to 25wt%.
6. The use according to claim 5, characterized in that: The solid content of the α-Al2O3 sol is 20wt%.
7. The use according to claim 1, characterized in that: The coating liquid preparation method comprises: stirring and mixing the raw materials according to the formula amount; the stirring speed is 500rpm~600rpm, and the stirring time is 1~2h.
8. The use according to claim 1, characterized in that: The sandblasting abrasive for the sandblasting pretreatment is silicon carbide; the particle size of the silicon carbide is 20nm-50nm.
Citation Information
Patent Citations
Method for preparing heat-resisting alumina-silox aerogel thermal-protective composite material
CN101792299A
Preparation method of antioxidant carbon block with heat and alkaline etching resistance
CN103130507A